PEMAAFAN MENUJU REKONSILIASI: FORGIVENESS TOWARD RECONCILIATION - Rahma Rizki Yuli; Dessy Pramudiani (Jurnal Psikologi Jambi, 2020)
Introduction Kerinci regency conflicts occur between villages such as conflicts that occur between Pendung Talang Genting village and Sleman village. This incident result in many physical, material losses and causes mental problems for the residents living in the village. Psychological problems that arise after conflict are deep trauma to children which causes fear to do activities outside the home. Forgiveness is one of the behaviors of someone who is a victim of conflict in improving relations. Purpose the research to knows how the description of forgiveness and the factors that influence the forgiveness of Pendung Talang Genting villagers towards Sleman after conflict villagers.Method This research using qualitative phenomenological approach, and data collection methods through interview techniques and data analysis use interpretative phenomenological analysis (IPA). The character of native Pendung Talang Genting village participants from 30 - 60 years old for women and men. they suffer financial, physical and even mental.Results The forgiveness of Pendung Talang Genting villagers are emotional, safe and comfortable priority, hollow forgiveness, forgiveness as an effort of reconciliation, and acceptance. The factors that influence forgiveness are religiosity, personality, and situation factors.Conclusions and Suggestions The four participants express forgiveness in the form of behavior. However, in reality participants have not been able to appreciate and feel the existence of forgiveness in themselves as a whole.The residents in the village should have start to create a sense of self to forgive so that conflict does nott occur so that the village will be comfortable and peaceful.Keywords: forgiveness, conflict, reconciliation, Kerinci Village ABSTRAK Latar Belakang Kerinci merupakan daerah yang rawan konflik antardesa. Konflik antardesa di Kabupaten Kerinci merupakan hal biasa terjadi, hampir setiap tahunnya terjadi konflik antardesa. Konflik yang terjadi antardesa Pendung Talang Genting dan desa Sleman memberikan banyak kerugian fisik, material dan menimbulkan masalah mental pada anak-anak dan ibu-ibu yang melihat konflik di desa Pentagen. Masalah psikologis yang timbul pasca konflik adalah trauma yang mendalam pada anak-anak yang menyebabkan ketakutan untuk melakukan aktifitas di luar rumah. Pemaafan merupakan salah satu perilaku seseorang yang menjadi korban konflik mampu memperbaiki hubungan. Tujuan Penelitian ini dilakukan untuk mengetahui bagaimana gambaran pemaafan dan faktor yang mempengaruhi pemaafan warga desa Pendung Talang Genting terhadap warga desa Sleman pasca konflik. Metode Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Metode pengumpulan data melalui teknik wawancara dan analisis data menggunakan interpretative phenomenilogical analisis (IPA). Karakter partisipan warga asli desa Pendung Talang Genting, usia 30 – 60 tahun, jenis kelamin laki-laki dan perempuan, meraka mengalami kerugian finansial dan fisik, dan menyaksikan langsung peristiwa konflik tersebut. Hasil Pemaafan warga desa Pendung Talang Genting yaitu emosional, prioritas rasa aman dan nyaman, hollow forgiveness, pemaafan sebagai upaya rekonsiliasi, dan penerimaan. Adapun faktor yang memengaruhi pemaafan adalah religiusitas, kepribadian, dan faktor situasi. Kesimpulan dan Saran keempat partisipan mengekspresikan pemaafan dalam bentuk perilaku. Namun dalam kenyataannya, partisipan belum dapat menghayati dan merasakan adanya pemaafan dalam dirinya secara utuh. Kata kunci: pemaafan, konflik, rekonsiliasi, Kabupaten Kerinci.